Critical evaluation of the Practical Legal Studies programme at the University of the Witwatersrand - Mahomed, Shaheda Hassim (My University, 2014)
Practical Legal Studies (PLS) generically referred to as Clinical Legal Education (CLE) — is a compulsory final year course offered as part of the LLB degree, at the University of the Witwatersrand (Wits). PLS was informally introduced at the University in 1969 initiated by law students as a means to gain practical experience as well as in an attempt to address the social imbalances in South African society through legal intervention. Today, PLS is one of only two courses at the University of the Witwatersrand that accommodates learning through the integration of theory and practice. The literature on CLE/ PLS rejects the practice that PLS be accommodated as an ‘isolated’ course within the law school curriculum but rather promotes that it be considered as a teaching methodology contemporarily referred to as experiential learning. Experiential learning promotes a teaching formula that comprises the integration of theory, practice and reflection. Furthermore, the CLE literature encourages and promotes that this formula be integrated into the entire legal curriculum. This thesis reviews the theory of learning, explores contemporary literature on CLE, provides a critical reflection on the goals, curriculum and teaching methodology attached to PLS at Wits and considers the potential integration of PLS methodology into mainstream LLB and LLM courses at Wits. The thesis thus uses the case study of PLS at Wits to argue that CLE as a teaching methodology is not capitalised to its maximum potential in South Africa. If, and when, PLS is seen as an instance of a broader teaching methodology to be adopted by the Wits Law School, PLS as an ‘isolated’ course will no longer continue, as the clinical methodology will be incorporated into all mainstream LLB and LLM courses.
Thesis (Ph.D.)--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Law, 2014.